Upaya Meningkatkan Hasil Belajar IPA dengan Menggunakan Strategi Pembelajaran Bowling Kampus pada Peserta Didik Kelas IV di SDN-3 Palangka Tahun Pelajaran 2016/2017: Efforts to Improve Science Learning Outcomes by Using Campus Bowling Learning Strategies in Class IV Students at Palangka Elementary School-3 in the 2016/2017 Academic Year - Bulkani Bulkani; Eceng Frista Wara (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to describe the learning activities of students using the Campus Bowling learning strategy. To improve science learning outcomes using the Campus Bowling learning strategy. The type of research used is Classroom Action Research (CAR) which has tried to solve or answer the problems faced in the current situation. The subjects in this study were 36 fourth grade students of Palangka Elementary School 3 in the Academic Year 2016, consisting of 24 male students and 11 female students. The qualitative and quantitative analysis techniques used are observation and tests. Data analysis uses the calculation of the average value and percentage of students' mastery of learning in classical. The results of the study concluded that the learning activities of students increased after going through the Campus Bowling learning strategy, namely in the first cycle with an average of 2.78 (quite good) and in the second cycle namely 3.42 (reasonable). There is also an increase in student learning outcomes after going through the Campus Bowling learning strategy, namely in the first cycle with an average of 54 with classical completeness of 45% (less achieved) and in the second cycle with a percentage of 73 with artistic integrity 100% (excellent).